Economic and Socio-Cultural Transformation of the Community in the Parangtritis Beach Tourism Area, Yogyakarta - Mauliddya Maharani; Ni Putu Dinda Apti Rahayu; Yunia Nisrawati Berisigep; Tania Selepia Br Sembiring; Firda Dia Lestari; I Putu Sriartha (Universitas Pendidikan Ganesha, 2026)
This study examines the social, economic, and cultural transformations of communities in the Parangtritis Beach Tourism Area Yogyakarta, in response to ecotourism development. The primary focus of this study is the influence of social and cultural capital on ecotourism success and its impact on changing employment patterns, economic resilience, community adaptation strategies, and the dynamics of local cultural identity. The results indicate that successful ecotourism management is strongly influenced by social capital such as collaborative networks, trust, and the value of mutual cooperation and cultural capital in the form of local wisdom, traditions, and community knowledge. The transformation of livelihoods from the primary sector to the tourism service sector is driven by economic, social, and external considerations such as the Covid-19 pandemic. Community economic resilience is tested by fluctuations in tourist visits, which are responded to with financial adaptation and business diversification. Furthermore, interactions between local communities and tourists bring changes at the sociocultural level, demonstrating the preservation of traditions such as Malam Jumat Kliwon (Friday Night Kliwon) and the Bekti Pertiwi Pinsung Ceremony, which remain alive amidst modernization. This study recommends the need for community capacity building and cross-stakeholder collaboration to ensure sustainable ecotourism development while maintaining local cultural identity.